2018
DOI: 10.1590/1807-3107bor-2018.vol32.0105
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear metallothionein in oral squamous cell carcinoma: clinicopathological parameters and patient survival

Abstract: The aim of this study was to identify the immunoexpression of methallothionein in oral squamous cell carcinoma as well as to address the correlation with clinical features, histological grade and patient survival. Samples were collected from 93 patients with tongue squamous cell carcinoma who presented for follow-up. Immunohistochemical expression of methallothionein in all groups was performed. The scoring system has previously been published by Tsurutani in 2005, which is based on intensity and distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
3
0
0
Order By: Relevance
“…The results presented confirm the findings of previous studies showing MTs overexpression in OLP [ 49 , 50 ], OL [ 51 , 52 ], and OSCC [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ] when each of these lesions was compared with normal oral mucosa. However, in the present study, we systematically analyzed the relationship of MTs expression between premalignant lesions and different grades of OSCC ( Figure 1 and Figure 2 ; Table 1 ).…”
Section: Discussionsupporting
confidence: 90%
“…The results presented confirm the findings of previous studies showing MTs overexpression in OLP [ 49 , 50 ], OL [ 51 , 52 ], and OSCC [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ] when each of these lesions was compared with normal oral mucosa. However, in the present study, we systematically analyzed the relationship of MTs expression between premalignant lesions and different grades of OSCC ( Figure 1 and Figure 2 ; Table 1 ).…”
Section: Discussionsupporting
confidence: 90%
“…This pathological entity commonly affects male individuals, such as those in the present study, belonging to an age group above 40 years and is frequently diagnosed in the sixth decade of life, which is in accordance with our results (33)(34)(35)(36)(37). Furthermore, it has been shown that the tongue and the floor of the mouth are the lesion sites in the majority of cases (23,31,34,38).…”
Section: Discussionsupporting
confidence: 93%
“…OSCC is the most common malignant neoplasm of the oral cavity (31,32). This pathological entity commonly affects male individuals, such as those in the present study, belonging to an age group above 40 years and is frequently diagnosed in the sixth decade of life, which is in accordance with our results (33)(34)(35)(36)(37).…”
Section: Discussionsupporting
confidence: 92%